Kinetics of extracting magnesium from prefabricated pellets by silicothermic process under flowing argon atmosphere - Guo J.-H.; Fu D.-X.; Han J.-B.; Ji Z.-H.; Dou Z.-H.; Zhang T.-A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The Pidgeon process is the main extraction method of magnesium, but its continuous production cannot be achieved due to the switch between vacuum and atmospheric pressure. Therefore, it is vital to realize continuous extraction of magnesium under atmospheric pressure. In this paper, the process of extracting magnesium from prefabricated pellets in flowing argon was proposed. The isothermal kinetic analysis of the reduction process was carried out. The results showed that the reduction process was controlled by diffusion process in 1 h, and the apparent activation energy of extracting magnesium from prefabricated pellets in flowing argon was 218.75 kJ/mol. Then the influence of experimental factors on the reduction rate was explored, including briquetting pressure, carrier gas flow rate, ferrosilicon content, reaction temperature and time. Through analysis and calculation, it was concluded that the main control step of diffusion process was silicon diffusion.